Arctic cut-off high drives the poleward shift of a new Greenland melting record - M. Tedesco; T. Mote; X. Fettweis; Edward Hanna; J. Jeyaratnam; J.F. Booth; R. Datta; K. Briggs (2016)
Large-scale atmospheric circulation controls the mass and energy balance of the Greenland ice sheet through its impact on radiative budget, runoff and accumulation. Here, using reanalysis data and the outputs of a regional climate model, we show that the persistence of an exceptional atmospheric ridge, centred over the Arctic Ocean, was responsible for a poleward shift of runoff, albedo and surface temperature records over the Greenland during the summer of 2015. New records of monthly mean zonal winds at 500?hPa and of the maximum latitude of ridge peaks of the 5,700±50?m isohypse over the Arctic were associated with the formation and persistency of a cutoff high. The unprecedented (1948–2015) and sustained atmospheric conditions promoted enhanced runoff, increased the surface temperatures and decreased the albedo in northern Greenland, while inhibiting melting in the south, where new melting records were set over the past decade.